2021
DOI: 10.1111/ped.14464
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of adhesive strapping for umbilical hernias of infants

Abstract: Background: Using a controlled trial, this study aimed to evaluate the effectiveness of adhesive strapping to improve the natural healing rate of umbilical hernia. Methods: This prospective, observational study included 128 patients from Kumamoto, Japan (97 in the adhesive strapping group, and 31 in observation group), from 2012-2015. The duration from first hospital visit to the hernia orifice closure was compared between the two groups. Result: Kaplan-Meier curves showed that the probability of umbilical her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…However, the adhesive strapping of the umbilicus is reportedly effective in treating early stage umbilical hernia and preventing umbilical skin protrusion 2–4 . Nevertheless, there are also reports of complications associated with adhesive strapping, many of which are mild skin disorders that occur in up to 41.2% of patients 4 . To our knowledge, this is the first report of two patients wherein severe skin complication (cellulitis due to compression gangrene) developed following adhesive strapping.…”
Section: Figmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the adhesive strapping of the umbilicus is reportedly effective in treating early stage umbilical hernia and preventing umbilical skin protrusion 2–4 . Nevertheless, there are also reports of complications associated with adhesive strapping, many of which are mild skin disorders that occur in up to 41.2% of patients 4 . To our knowledge, this is the first report of two patients wherein severe skin complication (cellulitis due to compression gangrene) developed following adhesive strapping.…”
Section: Figmentioning
confidence: 89%
“…Surgical treatment is recommended if hernias do not heal. However, the adhesive strapping of the umbilicus is reportedly effective in treating early stage umbilical hernia and preventing umbilical skin protrusion 2–4 . Nevertheless, there are also reports of complications associated with adhesive strapping, many of which are mild skin disorders that occur in up to 41.2% of patients 4 .…”
Section: Figmentioning
confidence: 99%
“…Spontaneous observation has the advantage of not requiring any treatment; however, it also has a disadvantage, such as in cases when the hernia orifice does not close or the umbilical protrusion remains after closure. Therefore, compression therapy has been proposed as a conservative treatment and is reported in several studies 2,4–8 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, compression therapy has been proposed as a conservative treatment and is reported in several studies. 2,[4][5][6][7][8] Compression therapy has the advantages of early closure compared with spontaneous observation 4,7,9,10 and a high rate of hernia…”
mentioning
confidence: 99%
“…Since the early 2000s, AS for UH has been positively recommended for earlier UH closure and a reduction in redundant skin of UH [ 3 ]. Additionally, a few observational studies have shown its excellent efficacy [ 4 , 5 ]. Moreover, AS for UH has been approved by the Japanese health insurance system since 2014; therefore, the number of facilities performing AS for UH has been increasing in Japan [ 3 ].…”
Section: Introductionmentioning
confidence: 99%